The reliability of force-velocity-power profiling during over-ground sprinting in children and adolescents - Melitta McNarry (Journal of Sports Sciences, 2019)
Anaerobic performance in youth has received little attention partly due to the lack of a “gold-standard” measurement. However, force-velocity-power (F-v-P) profiling recently showed high reliability and validity in trained adults. Therefore, the aim was to determine the reliability of F-v-P profiling in children and adolescents. Seventy-five children (60 boys, 15 girls; age: 14.1 ± 2.6 years) completed three 30 m sprints. Velocity was measured at 46.875 Hz using a radar device. The F-v-P profile was fitted to a velocity-time curve allowing instantaneous power variables to be calculated. Reliability was assessed using the intra-class correlation coefficient (ICC), coefficient of variation (CV), standard error of measurement (SEM) and smallest worthwhile change (SWC). High reliability was evident for absolute peak (Ppeak) and mean power (Pmean), Ppeak and Pmean expressed relative to body mass, peak and mean velocity, 30 m sprint time, peak horizontal force (F0), relative F0, mechanical efficiency index and fatigue rate (ICC: 0.75–0.88; CV: 1.9–9.4%) with time to peak power demonstrating moderate reliability (ICC: 0.50; CV: 9.5%). The F-v-P model demonstrated at least moderate reliability for all variables. This therefore provides a potential alternative for paediatric researchers assessing sprint performance and the underlying kinetics.